2019
DOI: 10.1186/s13039-019-0434-4
|View full text |Cite
|
Sign up to set email alerts
|

Deletions in the 17q chromosomal region and their influence on the clonal cytogenetic evolution of recurrent meningiomas

Abstract: Objective Meningiomas are among the most frequent intracranial tumors. Although the majority of meningiomas can be cured by surgical resection, up to 20% of the patients develop an aggressive clinical course with tumor recurrence or progressive disease. Cytogenetically, meningiomas frequently harbour a normal karyotype or monosomy of chromosome 22 as the sole anomaly. However, progression of meningiomas is associated with a non-random pattern of secondary losses of the chromosomes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Other frequent CNVs include chromosome 9p deletion, which contains tumor suppressor genes Cyclin-Dependent Kinase Inhibitor 2A and 2B (CDKN2A/B) [15], and loss of chromosomes 2p, 4p, 6q, 7p, 9p, 10q, 11p, 14q, 17q, and 18q [29][30][31][32][33][34][35][36][37]. Chromosome 2p loss is associated with choroid meningiomas, while anaplastic meningiomas demonstrate chromosome 1p, 6p, 14, and 22q losses [15].…”
Section: Somatic Copy-number Variationsmentioning
confidence: 99%
“…Other frequent CNVs include chromosome 9p deletion, which contains tumor suppressor genes Cyclin-Dependent Kinase Inhibitor 2A and 2B (CDKN2A/B) [15], and loss of chromosomes 2p, 4p, 6q, 7p, 9p, 10q, 11p, 14q, 17q, and 18q [29][30][31][32][33][34][35][36][37]. Chromosome 2p loss is associated with choroid meningiomas, while anaplastic meningiomas demonstrate chromosome 1p, 6p, 14, and 22q losses [15].…”
Section: Somatic Copy-number Variationsmentioning
confidence: 99%
“…Most small substituents in the meta-and para-positions were well tolerated. Compared with the naked aryl ring, halogens (12,13), electronwithdrawing groups (15,16), and electron-donating groups (18,19) all led to potency improvements. However, orthosubstituted derivatives (11,14,17) all led to a decrease in potency.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The title compound was prepared using S6 to give the product as an offwhite solid (32 mg, 80.3%). 27 1 4-(4-Fluoro-benzylamino)-quinazoline-8-carboxamide (13). The title compound was prepared using S6 to give the product as an offwhite solid (28 mg, 78%).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, technological developments have suggested that a higher rate of malignant meningiomas may be induced by increasing hypodiploidy, complex ablations, and even epigenetics (77)(78)(79)(80). Furthermore, certain characteristics have been correlated with histological subtypes, especially copy number alterations and mutations, suggesting a greater potential for gene therapy (58,80).…”
Section: Cytogenesis and Genomicsmentioning
confidence: 99%